KEPENTINGAN INGGRIS KELUAR DARI KEANGGOTAAN UNI EROPA TAHUN 2016 - Endy Anatta Pammasena; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This journal aims to determine the interest of United Kingdom for leaving European Union in 2016. The problems were started when United Kingdom’s Prime Minister, David Cameron, explained the situation of United Kingdom position within European Union that United Kingdom wanted European Union to be reformed and if it’s necessary, United Kingdom could leave the European Union. This was staggering because the United Kingdom and European Union relationship was really well since the European Single Market was established. In order to explain the problems, author uses the national interest theory. In this research there are four independent variables which is explained in chapter three, and three dependent variables which is explained in chapter four. From the research, author founds that United Kingdom left the European Union because there were policies made by European Union which could bring harm to the sovereignty of United Kingdom.Keywords: National Interest, United Kingdom Referendum